Investigation of Functional Activity of Cells in Granulomatous Inflammatory Lesions from Mice with Latent Tuberculous Infection in the New Ex Vivo Model - Elena Ufimtseva (Clinical and Developmental Immunology)
The new ex vivo model system measuring functional input of individual granuloma cells to formation of granulomatous inflammatory lesions in mice with latent tuberculous infection has been developed and described in the current study. Monolayer cultures of cells that migrated from individual granulomas were established in the proposed culture settings for mouse spleen and lung granulomas induced by in vivo exposure to BCG vaccine. The cellular composition of individual granulomas was analyzed. The expression of the leukocyte surface markers such as phagocytic receptors CD11b, CD11c, CD14, and CD16/CD32 and the expression of the costimulatory molecules CD80, CD83, and CD86 were tested as well as the production of proinflammatory cytokines (IFNγ and IL-1α) and growth factors (GM-CSF and FGFb) for cells of individual granulomas. The colocalization of the phagocytic receptors and costimulatory molecules in the surface microdomains of granuloma cells (with and without acid-fast BCG-mycobacteria) has also been detected. It was found that some part of cytokine macrophage producers have carried acid-fast mycobacteria. Detected modulation in dynamics of production of pro-inflammatory cytokines, growth factors, and leukocyte surface markers by granuloma cells has indicated continued processes of activation and deactivation of granuloma inflammation cells during the latent tuberculous infection progress in mice.